BIOACTIVITY STUDY OF MOSS DUMORTIERA HIRSUTA (SWAEGR.) NEES ETHANOLIC EXTRACT ON PARASITEMIC LEVEL OF PLASMODIUM BERGHEI VINCKE AND LIPS, 1948 IN MICE (MUS MUSCULUS L.) - Fathoni, Imam; Poerwanto, S. Herry; Astuti, R, R. Upiek Ngesti Wibawaning (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Malaria is a major infectious disease in the world including Indonesia. The main problem in controlling malaria is its resistance by standard treatment. Dumortiera hirsuta has not been widely used by the public as an alternative medicine. Liverworts contain bioactive compounds such as flavonoids, terpenoids, and alkaloids one of which may reduce the level of Plasmodium in the blood. Methods: Moss was collected from Telaga Putri waterfall, Yogyakarta. Samples were extracted by using 96% ethanol. Thin layer chromatography (TLC) was used for detecting bioactive compounds. Peter’s Suppressive Test method has been used for monitoring anti-plasmodial activities of moss extract in male SWISS Strain mice. The 107 P. berghei in 0.2 ml of DMSO were infected intraperitoneally for the treated mice (H0). There were 9 groups: 3 control groups, 1 placebo, and 5 treated groups on the 1st day (H1) until the 4th day (H4) D. hirsuta extract on 100; 200; 300; 400 and 500 mg/Kg BW doses were given orally. Results: The results of TLC showed that alkaloids, flavonoids, terpenoids, and saponins were detected in the extract of D. hirsuta. The most effective inhibition was showed at the dose 300 mg/Kg BW up to 96%, whether the control mice with chloroquine up to 77%. Conclusion: Ethanolic extract D. hirsutacould be potential source of an alternative antimalarial drug. Â